ANALISIS SUMBER DAN PENGGUNAAN KAS PADA CV GRIYA INDAH SEJAHTERA DI TENGGARONG - Sari, Rindayah Lukita (EKONOMIA, 2019)
Analysis of source and cash usage is basically an analysis performed to see cash flow that occurs within the company during certain period, both cash inflows and outflow cash flow. Cash flow (source of funds) and cash outflows (use of funds). Analysis of sources and use of cash will be known the structure of corporate financing in the period concerned, so it can know the accuracy (effectiveness) in the use of cash. The formulation of the problem in this study is whether the source and use of cash on CV.Griya Indah Sejahtera increased or decreased in 2014 until 2016. The purpose of this study to determine and analyze the increase and decrease of sources and cash usage in CV Griya Indah Sejahtera in year 2014 through 2016. Analysis tool in this research is comparison analysis on balance sheet and profit / loss then make classification of source and use of cash, then make report of source and use of cash. Research shows that the amount of cash (cash resources) in CV.Griya Indah Sejahtera Tenggarong 2014 period decreased by Rp -202.168.046, -, Year 2015 reduced by Rp - 41,711,416, - and in the period 2016 reduced Rp -18.241. 400, -. Thus, there has been a shortage of cash during the analysis period from 2014 to 2016, due to the greater amount of funds used to finance the operations of the company than the cash sources obtained, so that any cash receipts and management should be made good. Hence the hypothesis in this study is accepted.